Twistor Topology of the Fermat Cubic - Armstrong, J.; Salamon, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
We describe topologically the discriminant locus of a smooth cubic surface in the complex projective space CP³ that contains 5 fibres of the projection CP³⟶S⁴.